Values associated with public involvement in health and social care research: a narrative review. (10th December 2013) - Gradinger, Felix; Britten, Nicky; Wyatt, Katrina; Froggatt, Katherine; Gibson, Andy; Jacoby, Ann; Lobban, Fiona; Mayes, Debbie; Snape, Dee; Rawcliffe, Tim; Popay, Jennie
Abstract: Background: Much has been written about public involvement (PI) in health and social care research, but underpinning values are rarely made explicit despite the potential for these to have significant influence on the practice and assessment of PI. Objective: The narrative review reported here is part of a larger MRC‐funded study which is producing a framework and related guidance on assessing the impact of PI in health and social care research. The review aimed to identify and characterize the range of values associated with PI that are central elements of the framework. Methods: We undertook a review and narrative synthesis of diverse literatures of PI in health and social care research, including twenty existing reviews and twenty‐four chapters in sixteen textbooks. Results: Three overarching value systems were identified, each containing five value clusters. (i) A system concerned with ethical and/or political issues including value clusters associated with empowerment; change/action; accountability/transparency; rights; and ethics (normative values). (ii). A system concerned with the consequences of public involvement in research including value clusters associated with effectiveness; quality/relevance; validity/reliability; representativeness/objectivity/generalizability; and evidence (substantive values). (iii) A system concerned with the conduct of public involvement in including value clusters associated with Partnership/equality; respect/trust; openness and honesty; independence; and clarity (process values). Conclusion: Our review identified three systems associated with PI in health and social care research focused on normative, substantive and process values. The findings suggest that research teams should consider and make explicit the values they attach to PI in research and discuss ways in which potential tensions may be managed in order to maximize the benefits of PI for researchers, lay experts and the research.